1998
DOI: 10.1142/9789812817150
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Reflection of Shock Waves

Abstract: When writing can change your life, when writing can enrich you by offering much money, why don't you try it? Are you still very confused of where getting the ideas? Do you still have no idea with what you are going to write? Now, you will need reading. A good writer is a good reader at once. You can define how you write depending on what books to read. This propagation and reflection of shock waves can help you to solve the problem. It can be one of the right sources to develop your writing skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…By quantitative comparisons it was demonstrated that the branches undergo refraction in full agreement with Snell's law. These findings support an interpretation of the flux front dynamics at its fast initial stage as propagation of a damped shock electromagnetic wave of the kink type; see, e.g., [30]. We ascribe these waves to damped electromagnetic modes similar to those considered in Ref.…”
Section: -3supporting
confidence: 89%
“…By quantitative comparisons it was demonstrated that the branches undergo refraction in full agreement with Snell's law. These findings support an interpretation of the flux front dynamics at its fast initial stage as propagation of a damped shock electromagnetic wave of the kink type; see, e.g., [30]. We ascribe these waves to damped electromagnetic modes similar to those considered in Ref.…”
Section: -3supporting
confidence: 89%
“…In the 1950s of the previous century, many studies regarding the effect of the diaphragm opening time on the generated shock wave were published; examples are the works of Glass and Patterson [2], Henshall [3], White [4] and Shugaev et al [5]. However, only recently attention has been drawn to the effect that the ratio between the diaphragm open area and that of the tube cross section has on the generated shock wave.…”
Section: General State Of the Artmentioning
confidence: 99%
“…5 The thresholdvalue of focused laser beam intensity for creating breakdown in gases at optical frequencies is proportional to .I w 2 /=.t p 0 /, where I is the ionization potential, w is the frequency of laser radiation, t is the duration of laser pulse, and p 0 is the initial gas pressure. 10 Once the energy of the focused laser beam exceeds this value, ambient air breaks down with subsequentformation of laser plasma. This in turn generates an outward propagatingblast wave.…”
Section: Methodsmentioning
confidence: 99%